Seksualitas dan Reproduksi Perempuan dalam Karya-karya Sekar Ayu Asmara - Tineke Hellwig (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
The Reformation era has freed the media and public life in general from the tight binding of the New Order era, and enabled the emergence of many women in the realm ofIiterature and culture production. Now, it is not impossible to question the normative standard of the Suharto regime formed by authoritarianism, militarism and monolithic way of thinking. A number of cultural products (literature, theater, film) produced after 1998 focused on urban-cosmopolitan Iife and consumerist life style, and openly brought up issues related with woman sexuality and homophobia, which broke down a bunch of taboos and the common views in the society about heterosexuality, marriage and family values. Even though several woman writers and artists of this time have shown empathy to the celebration of woman sexuality and functioned to break down the "traditional" gender ideology, still some contemporary works support the masculine patriarchal point of view about woman sexuality and reproduction. Sekar Ayu Asmara is film director, script writer and novelist who represents woman in the conservative and even misogynic context. This paper discusses two of her novels, Pintu Terlarang (2004) and Kembar Keempat (2005). These works will be analyzed from the feminist perspective. Sekar's position, point of view andsexual politics will be discussed in a bigger framework about the production of culture by women.